Evaluasi Kelayakan Median Beberapa Ruas Jalan di Kota Palu - Barnabas, Peter L.; Kasan, Muhammad; Lestari, Sari Puji (Jurusan Teknik Sipil Universitas Tadulako, 2017)
The placement of median opening (U Turn) and the distance of inter median opening at several road in Palu city were indicated that it does not meet technical requirement so it can put the road user in dangerous situation which when the traffic flowing on the road grow higher then the risk of traffic accident will rise too. Moreover, the placement of median opening was indicated as an access road where as a place for specific activity beside the road. The existence of Garuda-Abd. Rahman Saleh as a T intersection also made an impact to the degree of saturation of certain road segment. The method that used to solve this study is based on the survey to collect the primary and secondary data MKJI 97 and median standard design analysis. The result shows that all of the placement median opening at several urban road links was not appropriate to the requirement standard then it needs reposition or any repairmen.